Reliability Analysis of Rainwater Harvesting Systems in Southern Italy. (2016) - Notaro, Vincenza; Liuzzo, Lorena; Freni, Gabriele
Abstract: Water scarcity is a current problem for many urban areas in the Mediterranean region due to the increasing water demand related to the population growth and the expansion of urban and industrialized areas. Climate change will intensify the pressure on water resources. Rainwater harvesting (RWH) may be an effective alternative water supply solution to face water scarcity. It has recently become a particularly important option in arid and semi-arid areas, mostly because of its many benefits and relative low costs. The present study aims to analyse the reliability of a RWH system installed to supply water for toilet flushing purpose with reference to a single-family house in a residential area of Sicily (Southern Italy). Historical water consumption data were analysed to obtain a flushing water demand pattern. A water balance simulation of the rainwater storage tank was performed, and the yield-after-spillage algorithm was used to define the tank release rule. The model's performance was evaluated using data from more than 100 different sites located throughout the Sicilian territory. This regional analysis provided results having practical applications, e.g. the identification of the optimal rainwater tank size and the annual system reliability curves as a function of mean annual precipitation. The uncertainty related to the regional model predictions was also assessed. Results showed that RWH systems can provide environmental and economic advantages in Sicily over traditional water supply methods. In particular, the regional analysis identified areas where the application of this system would be most effective.